P-small Compressible Modules and P-small Retractable Modules - ALHakeem, Mohammed Baqer; Al-Mothafar, Nuhad Salim (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
Let  be a commutative ring with 1 and  be left unitary  . In this papers we introduced and studied concept P-small compressible  (An     is said to be P-small compressible if  can be embedded in every of it is nonzero P-small submodule of . Equivalently,  is P-small compressible if there exists a monomorphism  , ,     is said to be P-small retractable if  , for every non-zero P-small submodule of . Equivalently,  is P-small retractable if there exists a homomorphism  whenever  as a generalization of compressible  and retractable  respectively and give some of their advantages characterizations and examples.